The POKEMON Speckle Survey of Nearby M Dwarfs. III. The Stellar Multiplicity Rate of M Dwarfs within 15 pc - Catherine A. Clark; Gerard T. van Belle; Elliott P. Horch; David R. Ciardi; Kaspar von Braun; Brian A. Skiff; Jennifer G. Winters; Michael B. Lund; Mark E. Everett; Zachary D. Hartman; Joe Llama (The Astronomical Journal)
M dwarfs are ubiquitous in our Galaxy, and the rate at which they host stellar companions, and the properties of these companions, provide a window into the formation and evolution of the star(s), and of any planets that they may host. The Pervasive Overview of “Kompanions” of Every M dwarf in Our Neighborhood (POKEMON) speckle survey of nearby M dwarfs is volume limited from M0V through M9V out to 15 pc, with additional targets at larger distances. In total, 1125 stars were observed, and 455 of these are within the volume-limited, 15 pc sample of M-dwarf primaries. When we combine the speckle observations with known companions from the literature, we find that the stellar multiplicity rate of M dwarfs within 15 pc is 23.5% ± 2.0%, and that the companion rate is 28.8% ± 2.1%. We also find that the projected separation distribution for multiples that are known to host planets peaks at 198 au, while the distribution for multiples that are not yet known to host planets peaks at 5.57 au. This result suggests that the presence of close-in stellar companions inhibits the formation of M-dwarf planetary systems, similar to what has been found for FGK stars.